117k views
1 vote
If the y-intercept of the function y=-(x+3)(2x-1)(x+b) is 12, what value must b represent?

1 Answer

4 votes

Answer:

your answer is the attached image below. Let me know if its right. I am 99.99% sure XD

Explanation:

How u get the answer is by Rewriting the equation as

-(x+3)(2x-1)(x+b)=12

Then you apply the distributive property. * = multiplication

(-x-1*3)(2x-1)(x+b)=12

Then multiply -1 by 3

(-x-3)(2x-1)(x+b)=12

Divide each term in the expression above by (-x-3)(2x-1) and simplify

(-x-3)(2x-1)(x+b) / (-x-3)(2x-1) =

12 / (-x-3)(2x-1)

Then simplify the left side, cancel the common factor of -x-3, and rewrite.

(2x-1)(x+b) / 2x-1 =

12 / (-x-3)(2x-1)

Now cancel the common factor of 2x-1, and divide x+b by 1

x+b=12 / (-x-3)(2x-1)

Simplify the right side, and factor -1 out of -x

x+b= 12 / (-(x)-3))(2x-1)

Rewrite -3 as 1(3)

x+b= 12 / (-(x)-1(3))(2x-1)

Factor -1 out of -(x)-1(3)

x+b= 12 / -(x+3)(2x-1)

Rewrite negatives (Rewrite -(x+3) as -1(x+3)

x+b= 12 / (x+3)(2x-1)

Move the negative in front of the fraction.

x+b= -12 / (x+3)(2x-1)

Subtract x from both sides of the equation.

b= -12 / (x+3)(2x-1)

There you go thats your answer! Hope it helped :)

If the y-intercept of the function y=-(x+3)(2x-1)(x+b) is 12, what value must b represent-example-1
User Serg Chernata
by
5.2k points